Phylogenetic Analysis of Mud Crab Scylla olivacea with Several Crustacean Based mRNA Encoding FAMeT - Yusuf, Sunarti; Tahya, Akbar Marzuki; Jamaluddin, Ruqayyah (AgriSains, 2020)
Previous studies have succeeded in isolating, and the basic sequence of mRNA encoding FAMeT Scylla olivacea. Several studies have noted that the FAMeT encoding mRNA sequence has differences in crustacean species. The aim of this study was to determine the relationship between S. olivacea and other crustaceans based on the FAMeT encoding mRNA sequence. The similarity of the FAMeT encoding mRNA sequences showed that several crustaceans had similarities to the FAMeT mRNA sequences of S. olivacea. The phylogeny tree analysis showed the existence of 2 clusters of the relationship between the mRNA encoding FAMeT of S. olivacea on the same branch as 2 other crab species: S. serrata and S. paramamosain. It was also found in Portunus trituberculatus and P. pelagicus and river prawn Macrobrachium rosenbergii. These findings indicated that the S. olivacea crab was monophyletic with 2 other mangrove crabs, namely the crab and the river prawn M. rosenbergii. So that describes a very close kinship relationship genetically. Meanwhile, the second branch consists of crustaceans such as Homarus americanus, Cherax quadricarinatus, Fenneropenaeus merguiensis, Metapenaeus ensis and Litopenaeus vannamei.